Persepsi Masyarakat terhadap Kualitas Pelayanan Pembayaran Pajak Kendaraan Bermotor di SAMSAT Kabupaten Serang - Yunica Marsha Sagina; Munawaroh Munawaroh (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to analyze public perceptions of the quality of motor vehicle tax payment services at SAMSAT Serang Regency. This research uses a quantitative approach with a survey method, where data is collected through a questionnaire in the form of a Likert scale. The research method used is descriptive statistical test, linear regression test and correlative test. distributed to taxpayers who have used services at SAMSAT. The results showed that public perceptions of service quality at Samsat Serang Regency were in the good enough category. This study recommends improving service quality through officer training, simplifying administrative procedures, and optimizing physical facilities at service locations. With these improvements, it is expected that taxpayer satisfaction and compliance in Serang Regency can increase sustainably.